Online dictionaries of English - Lew, Robert (My University, 2010)
In this paper I present an overview of the spectrum of available online English language dictionaries, and then offer some general comments on a few selected key issues. Given the current explosion of web content, it is quite pointless to try to list every single dictionary available. It makes better sense to identify the salient categories of online dictionaries and selectively focus on their prominent and typical representatives. The first notable category, so important to the many learners of English worldwide, are the famous British monolingual learners' dictionaries (the Big Five). Here, it is interesting to observe the gradual transition to the online medium in what has sometimes been called the freemium approach. Quality general English dictionaries aimed at the native speaker are not so well represented, but there are a wide choice of specialized (subject) dictionaries of varying quality and provenance. Special-purpose dictionaries include pronouncing dictionaries and onomasiological dictionaries. Diachronic dictionaries have also established a presence on the internet. As one guise of the Web 2.0 experience, we witness the emergence of bottom-up (or user-involvement) lexicography, with such prominent exemplars as the Urban Dictionary or Wiktionary. Hyperlinking is a fundamental feature of the web, but it is, arguably, overused in the so called dictionary aggregators: dictionary portals which put together entries from several online dictionaries. This creates highly redundant assemblages of lexicographic data. How to tap the richness of the Web but present the results in a user-friendly manner without laborious human intervention is a tough question. Another issue that still awaits satisfactory answers is the organization of access to data in online dictionaries. Even in highly respected dictionaries, there remain basic problems of access, such as with locating multi-word units, notwithstanding the upbeat tone of metalexicographers who often just pronounce the problem as essentially solved in the electronic medium. Other issues related to new technologies are the use of graphics, multimedia and alternative presentation modes, and these receive some attention. Finally, I play with the idea of the dictionary as an advanced query system sitting on top of a text corpus. Using collocation dictionaries as an example, I demonstrate that the difference between a sophisticated corpus query system and a more traditional lexicographic product may soon become something of a technical subtlety.
This is a preprint version of: Lew, Robert. 2011. ‘Online Dictionaries of English’ In Fuertes-Olivera, Pedro A. and Henning Bergenholtz (eds), E-Lexicography: The Internet, Digital Initiatives and Lexicography. London/New York: Continuum, 230–250.
Keywords: online dictionaries; English language; learners’ dictionaries; bottom-up lexicography; data access; multi-word units; graphics; multimedia